The Impementasi Problem Based Learning Dalam Pembelajaran IPA Di Kelas V Mi/SD: A. Konsep Pembelajaran Problem Based Learning (PBL) Atau Pembelajaran Berbasis Masalah, B. Implementasi Problem Based Learning dalam Pembelajaran IPA - Nadiyah, Mu'tiqoh Izzatun (Dharmas Education Journal (DE_Journal), 2022)
The purpose of this research is to improve science learning and student learning outcomes. With this research also aims to modify learning motivation on student achievement, to identify learning motivation, methods in education and school areas on student achievement. This research uses the Library Method sourced from books, journals, articles, Google Scholar or Google Scholar and others. The analysis made in this research is using content analysis. Content analysis is a research that is characterized by an in-depth study of the content of written or printed news in the media. The subjects of this study were students of class V, totaling 24 students. The results of the study show that the application of case-based learning can enhance the process and output of science learning for fifth grade students.